Integrating Ecology and Poverty Reduction The Application of Ecology in Development Solutions - Ingram, Jane Carter; DeClerck, Fabrice; Rumbaitis del Rio, Cristina (Springer New York : Imprint: Springer, 2012)
Integrating Ecology and Poverty Reduction offers a timely assessment of the current and potential role of ecological science and tools for contributing to poverty reduction.  The chapters in the first volume, Ecological Dimensions, address the ecological aspects of major development challenges and the contributions of ecological science to solving these problems. In the second volume, Application of Ecology in Development Solutions, authors address the roles and limitations of ecological science in creating longterm sustainable solutions to some of those problems and the social, economic and governance factors that mediate the implementation of these solutions. Integrating Ecology and Poverty Reduction is designed to illustrate the opportunities for ecological science to contribute to international development challenges and solutions; to foster new ways of thinking about the relationships between humans and the ecosystems in which they live; and to explore the tradeoffs and advantages in using an ecological approach to addressing poverty in a world of increasing population, high rates of poverty and continued ecological degradation.  The issues addressed and explored by experts in ecology and international development fields will be especially relevant for students and professionals interested in the intersection of poverty reduction and environmental sustainability.  About the Editors J. Carter Ingram is the lead of the Ecosystem Services and Payments for Ecosystem Services group at the Wildlife Conservation Society in New York, NY. Fabrice DeClerck is a professor of community and landscape ecology at CATIE in Costa Rica. Cristina Rumbaitis del Rio is an Associate Director at the Rockefeller Foundation in New York, NY. .